EFEKTIVITAS DAN EFESIENSI KEUANGAN TERHADAP DISTRIBUSI BBM PADA PT. ELNUSA PETROFIN (PERSERO) CABANG PAREPARE - Hasdiana, Hasdiana; Rahmad, Rahmad (Economos : Jurnal Ekonomi dan Bisnis, 2019)
This study has to determine the level of effectiveness and financial efficiency level of fuel distribution. The data collection techniques used in this study are, observation, interviews and documentation.  The data analysis technique used in this study used qualitative descriptive analysis and quantitative analysis techniques. The results of the study said that the financial effectiveness of fuel distribution in the year 2015 to 2016 decreased, while in 2016 to 2017 and 2018 increased with an average yield of 223% (belonging to the category very Effective). The financial efficiency rate of fuel distribution from 2018 to 2018 fluctuating with an average yield of 16.75% (including in efficient category).